In search of a telos: a critique of the performative green public sphere - Escrihuela,Carme Melo (2013)
This paper addresses the relationship between environmental politics and the public sphere. The focus is placed on the concept of the green public sphere, developed by Douglas Torgerson and very influential in green political theory. I argue that we should rethink Torgersons twin conceptions of environmental politics and the green public sphere. First, I review Torgersons Arendtian notion of the public sphere and explain why this view is limited as far as a transformative environmental politics is concerned. Drawing on the functions of public spheres in democratic theory, I stress that the merits of the green public sphere are to be evaluated not only in relation to the type of interaction they facilitate (rational-discursive), but especially to the extent that it is critical with power and influential on society and democracy. Then, I delineate an alternative account of the green public sphere better suited, in my opinion, to unfold its democratizing aspirations. To this end, I take into consideration Habermas notion and the further intellectual reactions it provoked.